Comparative study on sex hormone secretion in peripheral blood of women with common hematological tumors before and after chemotherapy - Liu, Liying; Zhou, Kexin; Yao, Liping; Hou, Rui; Zhu, Hui (Cellular and Molecular Biology, 2022)
This study aimed to explore the secretion of sex hormones in peripheral blood of women with common hematological tumors before and after chemotherapy. From January 2019 to April 2021, 100 female patients with common hematological tumors in our hospital were selected as the observation group, and 50 healthy women in our hospital during the same period were selected as the control group. The serum levels of follicle-stimulating hormone (FSH), estradiol (E2) and luteinizing hormone (LH) were detected and compared between the observation group and the control group before chemotherapy, patients with different disease types in the observation group, postmenopausal patients in the observation group, and postmenopausal patients in the observation group. Results showed that the serum FSH, E2 and LH levels of the observation group had no significant changes before chemotherapy (P > 0.05). Compared with before chemotherapy, the levels of serum FSH and LH in patients with different disease types in the observation group after chemotherapy were significantly higher, while E2 was significantly lower (P < 0.05), and the serum FSH, E2 and LH levels of postmenopausal patients in the observation group did not change significantly after chemotherapy (P > 0.05). The levels of FSH and LH in the observation group after chemotherapy were significantly higher, and E2 was significantly lower (P < 0.05). In general, the levels of sex hormone secretion in peripheral blood of women with common hematological tumors before and after chemotherapy can change significantly, especially in postmenopausal patients, but not in postmenopausal patients, which has a certain reference value for clinical practice.